An application of business process management in a dental clinic - Garcia, Bruna da Silva; de campos, Renato (Revista Gestão da Produção Operações e Sistemas, 2020)
Micro and small businesses are of great importance to the national environment of a country, due to their participation in economic growth. However, such businesses are characterized as poorly-managed, informal working environments, lacking both process organization and operational and strategic planning, and hence face difficulties in maintaining their position in the marketplace. In this context, the objective of this research was to analyze the case of a dental clinic located in a city from the interior of the state of Sao Paulo, Brazil, to understand and define the critical client service and stock management processes, through an application of the Business Process Management (BPM) model. The results show that BPM can be adapted for use with micro and small businesses, offering improvements and standardization for their most important processes.